Pengaruh Sarana Prasarana, Kualitas SDM dan Kemampuan Kerja Terhadap Kinerja Pegawai - Hasanuddin Hasanuddin; Eva Singgarniari; Faisal Faisal; Agussalim Ritonga; Imran Nasution; Supar Wasesa; Sri Rahayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect both jointly and partially between infrastructure, quality of human resources and work ability on employee performance at the Community and Village Empowerment Service (PMD) of Labuhanbatu Regency. This study uses quantitative methods with the type of explanatory research using primary data and secondary data. The population in this study were employees at the Department of Community and Village Empowerment (PMD) of Labuhanbatu Regency and as many as 52 employees were used as research samples. The data analysis technique used is multiple and partial linear regression using SPSS 24.0. The results of the regression analysis showed that of the three independent variables included in the regression model (infrastructure, quality of human resources and work ability). The infrastructure variable is significant at 0.016 so it can be concluded that infrastructure has an effect on employee performance (hypothesis 1 is accepted). HR quality variable which has a significant value at 0.000. So it can be concluded that the quality of human resources has an effect on employee performance (hypothesis 2 is accepted). The work ability variable which has a significant value is 0.007. So it can be concluded that work ability has an effect on employee performance (hypothesis 3 is accepted). The results showed that the variables of infrastructure, quality of human resources and work ability together had a positive effect on employee performance. This is evidenced by the statistical results of the regression test obtained a value with a probability of 0.000 is smaller than (α = 0.05), it can be explained that infrastructure, quality of human resources and work ability have a positive effect on employee performance. Then the fourth hypothesis is accepted.